A Comparison of External and Internal Factors Effecting the Decision to Choose to Pursue a Teaching Career Among Teachers from Different Background - Arpapant, Suwimon; Saengngam, Juthamas; Srihaset, Kamontip (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Education is one of the most important parts of a human being. One important component of education is the teacher. Apart from teaching, the teaching profession also has a role as an educator who has to educate the next generation of the nation. However, the teaching profession still encounters problems with selecting, recruiting, or maintaining the retention rate of teachers in the system. The objectives of this research were to (1) study the levels of external factors and internal factors that affect the decision to choose to pursue a teaching career among teachers from different backgrounds and (2) compare the external factors and internal factors that affect the teaching profession. Deciding on the teaching profession of teachers from different backgrounds. Methodology: The sample group used in this research were government and private school teachers. In the Eastern District, there were 3 districts, namely Min Buri District, Nong Chok District, and Saphan Sung District, with a total of 370 people using multi-stage random sampling. The research instrument was a questionnaire. The data was analyzed using a two-way multiple analysis of variance. Results: The results of the research found that (1) external and internal factors affect the decision to choose to pursue a teaching career among teachers from different backgrounds and the average is at a high level (M=4.14, SD=0.53 and M=4.41, SD=0.57 respectively). and (2) teachers with different educational qualifications have different levels of external factors and internal factors that affect their decision to pursue the teaching profession at the significant level of .05. As for teachers, there were no differences in the times of people of different age groups. Conclusion: Research highlights the important impact of both external and internal factors on teachers’ decisions to pursue teaching careers, regardless of their diverse backgrounds. Moreover, the influence of these factors differs significantly among teachers with different educational qualifications, especially as age is not an important factor in an individual’s decision to enter the teaching profession.